PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA PT. SUMBER MITRA KENCANA JAKARTA SELATAN - Febrianti, Tetin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2023)
ABSTRACTObjective: This study aims to determine the effect of job satisfaction and job stress on turnover intention both partially and simultaneously on the aluminum distributor company PT Sumber Mitra Kencana located in South Jakarta in 2018.Methodology: Employee in company PT Sumber Mitra Kencana located in South Jakarta. The data analysis method used is Path Analysis using the SPSS 20.0 program.Finding: The first, second, third, and fourth (H) hypotheses were accepted because the t statistic value was greater than t table, and the p value was smaller than alpha 0.05.Conclusion: The results indicate that: The job satisfaction variable has no significant effect on turnover intention; The work stress variable has a significant positive effect on turnover intention; and The variables job satisfaction and work stress have a significant positive effect on turnover intention. Suggestions in this research include: companies are expected to be able to create a better work environment, in order to maintain harmony between employees and all aspects of the company environment.Â